Coordinated targeting of cold and nicotinic receptors synergistically improves obesity and type 2 diabetes. Issue 1 (December 2018) - Clemmensen, Christoffer; Jall, Sigrid; Kleinert, Maximilian; Quarta, Carmelo; Gruber, Tim; Reber, Josefine; Sachs, Stephan; Fischer, Katrin; Feuchtinger, Annette; Karlas, Angelos; Simonds, Stephanie; Grandl, Gerald; et al.
Abstract Pharmacological stimulation of brown adipose tissue (BAT) thermogenesis to increase energy expenditure is progressively being pursued as a viable anti-obesity strategy. Here, we report that pharmacological activation of the cold receptor transient receptor potential cation channel subfamily M member 8 (TRPM8) with agonist icilin mimics the metabolic benefits of cold exposure. In diet-induced obese (DIO) mice, treatment with icilin enhances energy expenditure, and decreases body weight, without affecting food intake. To further potentiate the thermogenic action profile of icilin and add complementary anorexigenic mechanisms, we set out to identify pharmacological partners next to icilin. To that end, we specifically targeted nicotinic acetylcholine receptor (nAChR) subtype alpha3beta4 (α3β4), which we had recognized as a potential regulator of energy homeostasis and glucose metabolism. Combinatorial targeting of TRPM8 and nAChR α3β4 by icilin and dimethylphenylpiperazinium (DMPP) orchestrates synergistic anorexic and thermogenic pathways to reverse diet-induced obesity, dyslipidemia, and glucose intolerance in DIO mice. Tobacco smoking and cold exposure are environmental modulators of human energy metabolism suppressing appetite and increasing energy expenditure, respectively. Here, the authors develop a novel pharmacological strategy in which they simultaneously mimic the metabolic benefits of both phenomena through small-molecule combination therapy, and show that this treatment improves metabolic health of obese mice.